(untitled) (DAPesquisa, 2020)
Taking into consideration a scenario of environmental unsustainability where the fashion industry is placed, due to production and overuse of natural resources, together with the current economic development model, this work aims to investigate and synthesize strategies present in the literature related to design for sustainability to promote the confrontation of this scenario, as well as direct the practice of the fashion designer. The methodology employed in this study was guided by the integrative bibliographic review method associated to the graphical representation of synthesis, where a circular mandala was assembled with the intention of representing the synthesis of the proposed strategies. The study showed how, in fact, fashion designer has a great influence in the change to the new sustainable paradigm, to understand in depth the whole system of fashion, as well as to recognize the complexity and difficulties that demand new strategies for the development of products with a view to new lifestyles that respect the life cycle, expected in the dimensions that rule sustainable development.